A regularização fundiária urbana em seus aspectos notariais e registrais imobiliários - Menezes, Rossana Birck de (2024)
Guaranteeing the fundamental and social right to adequate housing is one of the greatest challenges today, which involves having access to a property to live in, which offers security, infrastructure, mobility and sanitation, among other characteristics necessary for a healthy quality of life. From this perspective, Law no. 13,465/2017, which governs the Urban Social Land Regulation (Reurb) with institutes that aim to title real estate property and legal security, the delegate agents of the extrajudicial service are fundamental actors in the development of Reurb procedures. This dissertation aims to study the performance and responsibility of delegated agents in carrying out acts within their competence in the application of Law no. 13,465/2017 and is justified because it deals with the execution and legal constitution of social rights. The need for studies and incentives on the matter is imminent, so much so that the right to the city is on the agenda of several national and international organizations with the aim of making cities inclusive, safe, resilient and sustainable. As secondary objectives, an analysis of direct actions of unconstitutionality that are being processed against the aforementioned legislation was carried out, in addition to identifying limits of action of delegated agents, relating responsibility criteria in the municipal legislation of Fortaleza/CE, highlighting the acts affected by the unrequirement of proof. of fiscal regularity, and verify the compliance of the exercise with a procedural bias. As a research problem, the question is what are the limits of action and, consequently, what are the obligations of delegate agents in the different types of Reurb? The methodology of a deductive approach is adopted in theoretical constructions, and for the procedural method, consultations with legislation, jurisprudential research and doctrinal studies are used. As a result of research, it is understood that the imposition of real estate titles, without providing adequate housing, can cause the opposite effect through gentrification and burden on the affected populations. Delegate agents have an important role in controlling legality, to prevent rights already conquered and guaranteed from being violated.